2021
DOI: 10.1021/acs.jafc.1c05657
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Broad-Specificity Starch Modification from the Crystal Structure of Limosilactobacillus Reuteri NCC 2613 4,6-α-Glucanotransferase GtfB

Abstract: GtfB-type α-glucanotransferase enzymes from glycoside hydrolase family 70 (GH70) convert starch substrates into α-glucans that are of interest as food ingredients with a low glycemic index. Characterization of several GtfBs showed that they differ in product- and substrate specificity, especially with regard to branching, but structural information is limited to a single GtfB, preferring mostly linear starches and featuring a tunneled binding groove. Here, we present the second crystal structure of a 4,6-α-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Biochemical characterization of this enzyme revealed that it is a 4,3-α-glucanotransferase (4,3-α-GTase), converting amylose/maltodextrins to a novel α-glucan with alternating (α1 → 3)/(α 1 → 4) linkages and with (α1 → 3,4) branching points. Overall, Lf2970 GtfB 4,3-α-GTase displayed high sequence identity with Lr121 GtfB 4,6-α-GTase, but homology models suggested that it has a more open binding groove, a feature that recently was shown to be present in about one in five of putative GtfB enzymes and was proposed to determine substrate (and product) specificity. , Moreover, Lf2970 GtfB 4,3-α-GTase has unique variations in some of the residues surrounding the substrate-binding groove, particularly in homology motifs I–IV. In GSs and GtfB, mutations in these motifs were shown to affect acceptor substrate binding and linkage specificity. ,,− …”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization of this enzyme revealed that it is a 4,3-α-glucanotransferase (4,3-α-GTase), converting amylose/maltodextrins to a novel α-glucan with alternating (α1 → 3)/(α 1 → 4) linkages and with (α1 → 3,4) branching points. Overall, Lf2970 GtfB 4,3-α-GTase displayed high sequence identity with Lr121 GtfB 4,6-α-GTase, but homology models suggested that it has a more open binding groove, a feature that recently was shown to be present in about one in five of putative GtfB enzymes and was proposed to determine substrate (and product) specificity. , Moreover, Lf2970 GtfB 4,3-α-GTase has unique variations in some of the residues surrounding the substrate-binding groove, particularly in homology motifs I–IV. In GSs and GtfB, mutations in these motifs were shown to affect acceptor substrate binding and linkage specificity. ,,− …”
Section: Introductionmentioning
confidence: 99%
“…Despite the low sequence similarity, the GbGtfC-ΔC core structure closely resembles that of GtfB-type 4,6-α-GTs. 18,25,26 Yet, PDBeFold analysis of the core domains (A, B, and C) of the GbGtfC-ΔC crystal structure revealed that the closest structural homologues are α-amylases from Alicyclobacillus sp. (PDB: 6GXV) 48 and Geobacillus stearothermophilus (PDB: 4UZU) 49 with Q-scores of 0.46/0.44 and root-mean-square deviations (RMSD) of 1.95/1.88 Å, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Residues H417 (motif II) and Y375 (370s loop) belong to the variable set of residues that have been suggested to affect product specificity in GtfB-type α-GTs. 26 Residue Y375 of GbGtfC is close to subsite +2 and may provide an aromatic stacking platform or a hydrogen bond; for the corresponding P968 of Lr121 GtfB, this is not the case. The larger side chain of Y375 also results in a more constrained acceptor binding space in GbGtfC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations